1971
DOI: 10.1002/app.1971.070151108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentration of atactic polypropylene on its rate of autoxidation

Abstract: SynopsisA general scheme previously reported for the autoxidation of polyolefins is further substantiated by results obtained for the uncatalyzed and catalyzed autoxidation of various concentrations of atactic polypropylene (APP) (by admixture with polyisobutylene) under various experimental conditions. Thus, rates of maximum carbonyl formation were measured as a function of APP concentration at 12OoC, oxygen concentrations ranging from 0.5%-100% by volume and cobaltic acetylacetonate catalyst concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…With the increment in nano-ZnO content, the initial decomposing temperature decreased, the maximal decomposing temperature, however, decreased then increased and finally approached that of pure NR. Previous studies [5][6][7] had shown that, the metal consists of variable valence would cause electron transferring and accelerate the production of free radicals to speed up the rupture of rubber hydrocarbons, resulting in the thermal degradation of rubber hydrocarbons and the production in ageing resistance. And the Zinc ion in the Nano-ZnO just possesses such a function.…”
Section: Thermal and Thermooxidative Ageing Resistancementioning
confidence: 99%
“…With the increment in nano-ZnO content, the initial decomposing temperature decreased, the maximal decomposing temperature, however, decreased then increased and finally approached that of pure NR. Previous studies [5][6][7] had shown that, the metal consists of variable valence would cause electron transferring and accelerate the production of free radicals to speed up the rupture of rubber hydrocarbons, resulting in the thermal degradation of rubber hydrocarbons and the production in ageing resistance. And the Zinc ion in the Nano-ZnO just possesses such a function.…”
Section: Thermal and Thermooxidative Ageing Resistancementioning
confidence: 99%